Increasing the length of EM-9 interstock enhances production efficiency in Imperial Gala apples - Filho J.L.M.* (2019)
© 2019 Universidade Federal de Vicosa.The objective of this study was to evaluate the influence of different lengths of EM-9 interstock, on the production and fruit characteristics of Imperial Gala apples more than eight years old. This experiment was conducted in a commercial orchard located in Vacaria-RS, Brazil, situated at an altitude of 955 m, during seasons 2005/06, 2007/08, 2010/11, 2011/12 and 2012/13. The treatments consisted of five lengths of EM-9 interstock (10, 15, 20, 25 and 30 cm) connecting the Marubakaido rootstock to the Imperial Gala scion. For production efficiency a positive correlation between increased efficiency and the length of interstock was observed. Likewise a positive correlation was also noted for quality parameters of the fruit; firmness and classification (Category 1). From this study we conclude that a EM-9 interstock of 30 cm on Marubakaido rootstock is the most suitable for the vigor control of Imperial Gala apples, it ensures greater production efficiency and firmer fruit.